Nasopharyngeal carriage of Streptococcus pneumoniae among children aged 30 days to <60 months in Beijing and Shenzhen, China (2018–2021) during pneumococcal conjugate vaccine introduction and the coronavirus disease (COVID-19) pandemic - Du, Qianqian; Liu, Zhaoqiu; Wang, Hongmei; Wang, Yani; Liu, Li; Wen, Xuexia; Yu, Sangjie; Ren, Qingqing; Gonzalez, Elisa; Arguedas, Adriano; Fletcher, Mark A.; Pan, Kaijie; et al. (Frontiers in Pediatrics, 2024)
Objectives: To describe the carriage rate, serotype distribution, and antimicrobial susceptibility patterns of Streptococcus pneumoniae (S. pneumoniae) nasopharyngeal (NP) isolates among healthy children aged 30 days to <60 months in the cities of Beijing and Shenzhen during 2018-2021. Methods: A NP swab sample was collected among four annual cohorts of healthy children at routine well-child visits. S. pneumoniae was identified by culture, optochin sensitivity and bile solubility, serotypes determined by latex agglutination and Quellung, and antimicrobial susceptibility testing performed using E-test strips. Results: S. pneumoniae NP carriage was 13.1% (645/4911), with the highest S. pneumoniae carriage prevalence (15.3%) observed in 25 to <60 months.The carriage prevalence was 15.1% in children 13 to 24 months, 13.2% in children 7 to 12 months, and 8.2% in children 30 days to 6 months (P < 0.01). Living with siblings pneumoniae carriage prevalence were found in the oldest age group (25 to < 60 months) and in children living with siblings or attending day-care. Vaccination with PCV7 or PCV13 was associated with lower PCV13-serotype colonization. In Beijing, S. pneumoniae carriage significantly declined during the COVID-19 pandemic.